Implementing the Controller Area Network (CAN) Protocol for Multiplex System - Zarina , Mohd Noh; Muzalifah, Mohd Said; Norhidayah, Mohamad Yatim; Rostam Affendi, Hamzah (2010)
Controller Area Network (CAN) protocol can be implemented in networking a system by the application of PIC18F458 microcontroller and MCP2551 transceiver. For successful transmission, design specification concerning the CAN node identifier assignment, message reception pattern and time synchronizatio must be determined accordingly. The CAN network developed in this article performs a simple application of transmitting a one-byte data through a three-node network. This eye-opener CAN system realization may act as a platform for researchers who are interested in the application of CAN protocol in networking a multiplex system. The work can also be used for analyzing purposes concerning the CAN usage in domestic embedded system application networking.